Efikasi Kain Bahan Furnitur Berinsektisida Malation terhadap Kematian Aedes aegypti - Hubullah Fuadzy; Susi Soviana; Risa Tiuria (ASPIRATOR - Journal of Vector-borne Disease Studies, 2018)
Implementation of fogging using malathion impacted to insecticides deposited to household furniture in resident. The other hand, Ae. aegypti preference resting on that furniture. The objective was determine lethal concentration of malathion in an emulsifiable concentrate (EC) formulation which have been deposited on furniture fabrics against mortality of Ae. aegypti. The study was true experimental and completed randomize design. Treatment as much as six of concentration levels (0.00; 0.27; 0.29; 0.31; 0.32; 0.34%) and ten replications. The sample were female Ae. aegypti on ovary condition of unfed and bloodfed. Material of fabrics used were cotton, chenille, and blackout. Procedure efficacy test based on WHO (2013). The result showed that between concentration levels gave a significantly different impact of mortality, but between concentration of 0.27% with 0.29% was not significantly. Mortality of Ae. aegypti reached 100% on 0.34% concentration for cotton and blackout, whereas chenille on 0.31% concentration. Lower lethal concentration to kill 50% and 95% Ae. aegypti population were 0.260% and 0.301% on chenille, whereas the higher were 0.296% and 0.337% on cotton, respectively. Conclusion was malation (EC) which were deposited to cotton, chenille, and blackout fabrics as a upholstery for furniture influence on increasing insecticide efficacy to Ae. aegypti.